Posttraumatic stress and growth in childhood cancer survivors: Considering the pathways for relationship - Koutná, Veronika; Blatný, Marek; Jelínek, Martin (Journal of psychosocial oncology, 2021)
PURPOSE: This study aims to contribute to the clarification of posttraumatic stress symptoms (PTSS) and growth (PTG) in childhood cancer survivors, taking into account the possibility of a nonlinear relationship and using a clinical approach to analyzing PTSS. METHODS: Childhood cancer survivors (n = 167) aged 11-27 completed measures of posttraumatic stress (UCLA_PTSD) and posttraumatic growth (BFSC). Based on the clinical analysis of UCLA_PTSD symptoms, the sample was divided into three PTSS severity groups (no, mild, moderate). These groups were compared in the mean level of PTG. Correlation analysis was performed to analyze the relationship of PTG with overall PTSS as well as its subscales. The analysis was completed using the curve estimation procedure evaluating linear and quadratic curve fit. RESULTS: There was no significant difference in the mean PTG scores between the three PTSS severity groups and no significant correlation of PTG with overall PTSS score and its clusters (re-experiencing, avoidance and increased arousal). PTG was positively associated with the fear of cancer recurrence. CONCLUSION: We did not find support for the direct relationship of PTG and PTSS but we suggest the possibility of connection between the two through the specific nature of PTSS in cancer survivors and their future-oriented intrusive thoughts overlapping with fear of cancer recurrence. These findings offer a novel perspective for future research on PTSS and PTG relationship.
Keywords: Young Adult; posttraumatický růst; Male; Neoplasms; mladý dospělý; Adolescent; Child; Cancer Survivors; dítě; Adult; dospělí; mužské pohlaví; mladiství; Stress Disorders, Post-Traumatic; Childhood cancer survivors; lidé; ženské pohlaví; Posttraumatic Growth, Psychological; Humans; posttraumatická stresová porucha; nádory; přežívající onkologičtí pacienti; posttraumatic growth; posttraumatic stress; Female; fear of cancer recurrence